Primäres Plattenepithelkarzinom der Gallenblase als seltene Ursache für eine akute Cholezystitis = Acute squamous cell carcinoma of the gallbladder - a rare cause of acute cholecystitis - Damian, Ulrich; Rumstadt, Bernhard; Schilling, Dieter (Deutsche medizinische Wochenschrift, 2011)
History and admission findings: A 54-year-old woman with signs of acute cholecystitis but no other relevant diseases was admitted into our hospital. Investigations: The abdominal ultrasonography showed an acute cholecystitis with possibly an abscess in the bed of the gallbladder (DD gall bladder cancer). Therefore a laparoscopy was performed which revealed a tumorous infiltrating the adjacent organs. A R1 resection was performed. Diagnosis, treatment and course: The histological examination revealed the rare finding of a squamous cell cancer of the gall bladder. On advice of our tumor board, chemotherapy with cisplatin and 5-flourouracil was initiated. Tumor-associated bile duct stenosis required endoscopic stent implantation. Despite the poor prognosis the disease remained stable 18 month later, with a Karnofsky index of 100%.Conclusion: Squamous cell carcinoma of the gallbladder is rare and requires a good interdisciplinary management. In an individual setting it is possible to increase survival with interdisciplinary treatment and palliative chemotherapy.
Gesehen am 08.05.2023